Towards PWA in Healthcare - Rego, Felipe (2019)
Nowadays there is a very large number of mobile applications that use the network to offer some functionality to users and because of this, applications are limited by the network conditions, such as network latency. These mobile applications usually are developed in a traditional approach, designated as a native approach and its goal is to develop the application to a specific operating system (iOS, Android). Applications used in a working environment are known to improve its process, but the network has the potential to decrease application performance and traditional mobile development is inefficient. Healthcare is a field with huge opportunities for application development because applications have the potential to improve work efficiency and quality of patient care. This paper consists of introducing the Progressive Web Application mobile development approach in the healthcare industry as an m-Health solution. It highlights successful cases of such an approach and key features, that allow establishing a reliable and resilient mobile application, that deals with most challenges involving the network nowadays and is a valid opportunity in the healthcare business. This document also presents a mobile health application for dietary evaluation, compares the PWA approach and other traditional approaches with a SWOT Analysis, PWA success cases, the INTCare system (an intelligent decision support system available in the Centro Ho spitalar do Porto) and the opportunity to use Progressive Web App in the INTCare's Electronic Nursing Record (ENR), which is a web interface that represents clinical patient information, integrated in a new proposed INTCare system architecture design. (C) 2019 The Authors. Published by Elsevier B.V.